2008
DOI: 10.1212/01.wnl.0000318294.36223.69
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of blood pressure variability after thrombolysis in acute stroke

Abstract: Blood pressure variability is associated with greater diffusion-weighted imaging lesion growth and worse clinical course in patients with stroke treated with IV tissue plasminogen activator. However, its impact varies depending on the occurrence of early recanalization after thrombolysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
102
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(114 citation statements)
references
References 20 publications
5
102
3
Order By: Relevance
“…In the setting of LVO patients treated with intravenous thrombolysis, BP variability was shown to be associated with Diffusion Weighted Imaging lesion growth and 90‐day outcome, especially in non‐recanalizers 15. By contrast, we did not find an interaction with recanalization status, which might partly be explained by the modest number of BP collected after recanalization.…”
Section: Discussioncontrasting
confidence: 76%
“…In the setting of LVO patients treated with intravenous thrombolysis, BP variability was shown to be associated with Diffusion Weighted Imaging lesion growth and 90‐day outcome, especially in non‐recanalizers 15. By contrast, we did not find an interaction with recanalization status, which might partly be explained by the modest number of BP collected after recanalization.…”
Section: Discussioncontrasting
confidence: 76%
“…As mentioned earlier, the second ECASS study cohort has reported that higher the systolic pressure before and after t-PA injection, higher the risk of PH 7 . There have also been studies suggesting that risk factor of PH is not systolic pressure before t-PA injection, but systolic pressure 24 hours post-injection 13,14 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, ischemic penumbra indicates a state hypoperfusion when the blood pressure of the body is reduced or hyperfusion when the blood pressure of the body is increased. The reason behind larger BP variability negatively affecting the patient's prognosis is the changes in blood flow of the ischemic penumbra around the ischemic stroke lesion 13,15 .…”
Section: Discussionmentioning
confidence: 99%
“…This evidence is supported by spontaneous reductions in BP after recanalization 34 and increases in infarct volume in the setting of large BP fluctuations without recanalization. 35 Furthermore, hemorrhagic transformation after thrombolytic therapy, consistent with recanalization and the potential for increased brain edema, was associated with a trend toward lower SBP. 36 Conversely, in the setting of thrombolytic therapy, there is significant evidence supporting an association with elevated BP and intracerebral hemorrhage.…”
Section: Blood Pressure Management In the Setting Of Thrombolytic Andmentioning
confidence: 93%